Ectopic and visceral fat deposition in lean and obese type 2 diabetes patients - Levelt, E; Pavlides, M; Banerjee, R; Mahmod, M; Kelly, C; Sellwood, J; Ariga, R; Thomas, S; Francis, J; Rodgers, C; Clarke, W; Sabharwal, N; et al. (Elsevier, 2016)
BACKGROUND- Type 2 diabetes (T2D) and obesity are associated with non-alcoholic fatty liver disease, cardiomyopathy and cardiovascular mortality. Both conditions showed stronger links between ectopic and visceral fat deposition and increased cardio-metabolic risk than subcutaneous fat deposition. OBJECTIVES- We tested the hypothesis that even lean patients with T2D (Ln-T2D) exhibit increased ectopic and visceral fat deposition, and that these are linked to cardiac and hepatic changes. METHODS- Twenty-seven obese (Ob-T2D), fifteen Ln-T2D with no other comorbidities, and twelve age matched controls were studied. Patients underwent cardiac CT (epicardial fat volume quantification), cardiac MRI (volumes and function), 31P-MRS (myocardial PCr/ATP), 1H-MRS (myocardial triglyceride) and multi-parametric liver MRI (1H-MRS hepatic triglyceride; T1- and T2*-mapping yielding 'iron-corrected T1' [cT1], a measure of hepatic fibrosis and inflammation). Healthy, lean subjects underwent identical MRI protocols. RESULTS- Diabetes, even in the absence of obesity, was associated with increased myocardial triglyceride content (p=0.01), hepatic triglyceride content (p=0.04) and impaired myocardial energetics (p=0.04). While cardiac structural changes, steatosis and energetics were similar between the T2D groups, epicardial fat (p=0.04), hepatic triglyceride (p=0.01) and insulin resistance (p=0.03) were higher in Ob-T2D. Epicardial fat, hepatic triglyceride and insulin resistance correlated negatively with systolic strain and diastolic strain rates which were only significantly impaired in Ob-T2D (p Greater than 0.001 and p=0.006, respectively). Fibroinflammatory liver disease (elevated cT1) was only evident in Ob-T2D (p=0.004 and p Greater than 0.001 vs Ln-T2D and controls, respectively). cT1 correlated with hepatic and epicardial fat (p Greater than 0.001 and p=0.01 respectively). CONCLUSIONS- Irrespective of BMI, diabetes is related to significant abnormalities in cardiac structure, energetics, cardiac and hepatic steatosis. Obese patients with T2D show a greater propensity for ectopic and visceral fat deposition that is associated with cardiac dysfunction, fibroinflammatory liver disease and insulin resistance.